2014
DOI: 10.1111/jpi.12123
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates Echis carinatus venom‐induced toxicities by modulating inflammatory mediators and oxidative stress

Abstract: Viper bites cause high morbidity and mortality worldwide and regarded as a neglected tropical disease affecting a large healthy population. Classical antivenom therapy has appreciably reduced the snakebite mortality rate; it apparently fails to tackle viper venom-induced local manifestations that persist even after the administration of antivenom. Recently, viper venom-induced oxidative stress and vital organ damage is deemed as yet another reason for concern; these are considered as postmedicated complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…In in vivo studies, the administration of melatonin along with antivenom significantly reduced the Nn venom‐induced oxidative stress and as well as inflammatory markers. This is in line with our earlier study carried out in the recent past, where the melatonin effectively reduced the E. carinatus venom‐induced toxicity by modulating inflammatory mediators and oxidative stress . In pre‐incubation experiments, the administration of melatonin alone not only increased the survival time of Nn venom‐injected mice but also offered complete protection when administered in combination with half effective dose of antivenom (group VI), while antivenom alone offered complete protection at effective dose (group IV).…”
Section: Discussionsupporting
confidence: 90%
“…In in vivo studies, the administration of melatonin along with antivenom significantly reduced the Nn venom‐induced oxidative stress and as well as inflammatory markers. This is in line with our earlier study carried out in the recent past, where the melatonin effectively reduced the E. carinatus venom‐induced toxicity by modulating inflammatory mediators and oxidative stress . In pre‐incubation experiments, the administration of melatonin alone not only increased the survival time of Nn venom‐injected mice but also offered complete protection when administered in combination with half effective dose of antivenom (group VI), while antivenom alone offered complete protection at effective dose (group IV).…”
Section: Discussionsupporting
confidence: 90%
“…It also mitigates the oxidative stress and vital organ damage induced by venom of the viper Echis carinatus in mice (Katkar et al, 2014). Because of the previously reported protective effects of melatonin against venom from a variety of sources, we investigated whether melatonin would be effective against N. haje venom-induced toxicity in the liver, kidneys, and heart of rats.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin ( N ‐acetyl‐5‐methoxytryptamine), an indoleamine, is synthesized by the pineal gland and also produced by peripheral organs such as retina, Harderian gland, gut, and skin . Melatonin has been shown to exert biological activities, including antioxidative, anti‐inflammatory, and anti‐apoptotic properties . Previous studies have demonstrated that melatonin exhibits powerful hepatoprotective effects in a series of liver injury models, including ischemia/reperfusion, viral hepatitis, liver fibrosis, and heavy metal‐induced liver injury .…”
Section: Introductionmentioning
confidence: 99%